INPUT SHAPING CONTROL TO REDUCE RESIDUAL VIBRATION OF A FLEXIBLE BEAM - Nguyen, Quoc Chi; Ngo, Ha Quang Thinh (Journal of Computer Science and Cybernetics, 2016)
In this paper, three control algorithms based on input shaping method are developed to suppress the residual vibration of a flexible beam. The flexible beam is modeled as an under-damped system. Three input shapers, ZV, ZVD, and ZVDD, are used to control the flexible beam. The three control algorithms are implemented by using the Mechatrolink-III motion system. The experiments are performed to verify the effectiveness of the three control algorithms